Power 5G Hybrid Networking and Security Risk Analysis - Jiang, Yu; Cong, Yang; Hu, Aiqun (Frontiers in Energy Research, 2022)
5G communication technology provides strong support for the power Internet of Things, and it also introduces new security challenges in the application process of the power industry. Starting from the analysis of the power 5G business requirements, this paper proposes five 5G enterprise networking construction plans based on different collaborative processing relationships, and conducts a comparative analysis in some aspects. According to the analysis of power business requirements and enterprise networking mode, a hybrid networking architecture of 5G and power communication network is proposed, and the 5G network slicing architecture is re-segmented according to different business scenarios. Finally, from the four parts of terminal access, edge computing, network channel and core network, the new risks and challenges introduced by 5G technology are analyzed in detail.